Implementasi Bank Garansi dalam Kontrak Konstruksi antara Pemerintah dan Kontraktor di Dinas Pekerjaan Umum dan Penataan Ruang Kota Bengkulu - I Gusti Yesi Triastiti; Candra Irawan; Emelia Kontesa (Law Department, Sharia and Law Faculty., 2022)
This research is to find out how the implementation of the Bengkulu City Public Works and Spatial Planning Service towards the Bank Guarantee in the event of a default from the service provider and legal protection for the parties in the construction contract in the event of a default the bank guarantee does not fulfill its obligations. This type of re-search is empirical research using qualitative methods. Data was collected by means of interviews and literature study of secondary data. The results of this study indicate: (1). That the Implementation of the Bengkulu City Public Works and Spatial Planning Ser-vice has the right to make a guarantee disbursement due to a default by the service provider. (2). Legal Protection for Service Providers if the bank does not disburse the guar-antee, the service provider can file a lawsuit against the bank for unlawful acts. The pro-vider also suffers a loss because the Service Provider who is in default still compensates for the loss to the Service User.